USM SIGNS MOU WITH HADHRAMOUT ESTABLISHMENT FOR HUMAN DEVELOPMENT YEMEN 7 NOVEMBER 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 31 October 2016 Universiti Sains Malaysia (USM) would be having a ceremony to sign a Memorandum of Understanding (MoU) with Hadhramout Establishment for Human Development (HEHD) Yemen on Monday, 7 November 2016, at 11.00 am at the Chancellory Conference Room, Level 6, Chancellory Building USM.